THE PROBATIVE VALUE OF POST-OFFENCE CONDUCT EVIDENCE - BC Naudé (Obiter, 2021)
In certain circumstances, post-offence conduct can provide circumstantial evidence of guilt. It is, however, often difficult to state why a particular type of post-offence conduct makes guilt probable. The objective of this contribution is to identify principles that could assist in determining the probative value of certain types of postoffence circumstantial evidence. It is shown, with reference to specific types of postoffence conduct, that it is mostly speculative to make any inference from such evidence. In the end, it is submitted that the principles governing the assessment of circumstantial evidence will only allow an inference of guilt to be drawn from postoffenceconduct if the inference was established beyond a reasonable doubt. It will not be enough to draw an inference from facts which were not, themselves, proved beyond a reasonable doubt, but which were merely accepted upon reasonable grounds.